Factors Affecting Smartphone Purchase Decisions of Generation-Y - Shabrin, Nushrat; Khandaker, Sarod; Kashem, Saad Bin Abul; Hie, Chan Kit; Susila, Teresa (The journal of contemporary issues in business and government, 2017)
Smartphones have become an indispensable part of daily life of Generation- Currently, Generation-Y accounts for the biggest proportion of the Malaysian population, and they are the main users of smartphones. The main objective of this research is to determine the factors influencing the smartphone purchase decisions of Generation-Y. Based on a literature review and survey, this study finds seven factors that influence smartphone purchase decisions: brand, convenience, dependency, price, social influence, product feature and social needs. The research used a questionnaire with a 5-point Likert scale for data collection and a sample of 152 respondents (Generation-Y) from the Kuching region of Malaysia. We find evidence that social influence, product feature, and brand image have significant positive impacts on the smartphone purchasing decisions. Other factors, such as convenience, dependency, price and social needs were statistically insignificant.